2006
DOI: 10.1080/09638280500301584
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of weakness in the upper and lower limbs post-stroke

Abstract: Although group analysis showed that the leg was significantly stronger than the arm, individual analysis showed that most participants had a similar degree of weakness in both limbs. When there was a difference, the lower limb was more frequently the stronger. Proximal joints were not more severely affected than distal joints. Patient demographics and stroke pathology factors were not associated with weakness, but stroke-related impairments were.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Weakness may affect all muscle groups of the upper limb, or may be selective, affecting some muscle groups more than others. Large inter-subject differences exist in the pattern of muscle weakness across muscle groups, but research has shown that no consistent proximal-to-distal gradient or greater extensor relative to flexor weakness exists (Mercier and Bourbonnais 2004; Tyson, Chillala et al 2006). While the absolute strength in any particular muscle group has not shown to predict function, the rate of change of force development in wrist extensor and handgrip strength (Renner, Bungert-Kahl et al 2009) are good predictors of upper limb function.…”
Section: Learned Nonusementioning
confidence: 99%
“…Weakness may affect all muscle groups of the upper limb, or may be selective, affecting some muscle groups more than others. Large inter-subject differences exist in the pattern of muscle weakness across muscle groups, but research has shown that no consistent proximal-to-distal gradient or greater extensor relative to flexor weakness exists (Mercier and Bourbonnais 2004; Tyson, Chillala et al 2006). While the absolute strength in any particular muscle group has not shown to predict function, the rate of change of force development in wrist extensor and handgrip strength (Renner, Bungert-Kahl et al 2009) are good predictors of upper limb function.…”
Section: Learned Nonusementioning
confidence: 99%
“…Sensorimotor deficits in the upper limb, such as weakness (Bourbonnais & Vanden Noven, 1989;Dewald & Beer, 2001;Tyson, Chillala, Hanley, Selley, & Tallis, 2006), decreased speed of movement (Trombly, 1992), decreased angular excursion and impaired temporal coordination of the joints (Cirstea & Levin, 2000;Levin, 1996), impaired upper-limb and trunk coordination (Cirstea & Levin, 2000;Michaelsen, Luta, Roby-Brami, & Levin, 2001), and impaired hand function (Lang, Wagner, Edwards, Sahrmann, & Dromerick, 2006;Welmer, Holmqvist, & Sommerfeld, 2008), may limit the ability to use the affected upper extremity to perform various tasks.…”
mentioning
confidence: 99%
“…HSP on movement is a predictor of poor functional outcome (Pong et al, 2012;Roy, Sands, Hills, Harrison, & Marshall, 1995) while poor motor recovery has been associated with presence of HSP (Pong et al, 2012;Smith, 2012). Immobility of the upper limb due to paralysis or weakness (Ada et al, 2003;Tyson, Chillala, Hanley, Selley, & Tallis, 2006) and changes in muscle control and adaptive changes in muscle length post-stroke (Ada et al, 2003;Kalichman & Ratmansky, 2011) and inwards/outwards (medio-laterally). The mobility of the glenohumeral joint together with joint instability puts it at risk of musculoskeletal complications post-stroke (Shepherd & Carr, 1998).…”
Section: Adey-wakelingmentioning
confidence: 99%